Assessment of the creditworthiness of mineral complex enterprises - issuers of the stock market - V. M. Zaernyuk (Известия высших учебных заведений: Геология и разведка)
A low awareness of the events, influencing on the stocks prices, is an important factor of the decline of the inner investors’ credibility to the investments in risky assets. The article examines the methodological features of the credit assessment of mineral complex enterprises, which are the issuers of the securities market. An approach to assessing the creditworthiness of corporate issuers is given, which includes theoretical and methodological basis and methodology for assessing credit rating, being an an integrated credit risk characteristic, reflecting the likelihood of untimely or incomplete fulfillment by the issuer of its obligations. Boundaries of the intervals of possible values of analyzed factors of quantitative analysis and distribution of the coefficients for the intervals of possible values for assessing the financial condition of the issuer are designed.